Customer Loyalty: The Difference between Full-Service Carriers and Low-Cost Carriers in Indonesia - Yasintha Soelasih; Sumani Sumani (Bina Nusantara University, 2021)
The level of competition in the aviation industry has increased since the regulation change in 1999. Aviationcompanies in providing services can be divided into three categories: full service, medium service, and no-frillsservice. Both Full-Service Carriers (FSCs) and Low-Cost Carriers (LCCs) experience a high level of competition.The research aimed to look at the differences in customer loyalty on domestic FSCs and LCCs in Indonesia.The differences were shown from testing the effect of service quality on customer loyalty mediated by customersatisfaction and behavioral intention to use. Respondents were FSCs and LCCs passengers. Samples were takenby purposive sampling. There were 522 respondents for FSCs and 529 respondents for LCCs were observed bydistributing questionnaires. Then, the research tested the validity and reliability of the variables using ConfirmatoryFactor Analysis (CFA), Composite Reliability (CR), and Average Variance Extracted (AVE). Structural EquationModeling (SEM) was also applied to examine the hypothesis. The results show the formation of customerloyalty from service quality, customer satisfaction, and behavioral intention to use on FSCs and LCCs. The mostsignificant factor is the behavioral intention in forming customer loyalty in FSCs and LCCs. Meanwhile, customersatisfaction does not influence customer loyalty for FSCs and LCCs.